Countdown 1960 : the behind-the-scenes story of the 312 days that changed America's politics forever - Wallace, Chris; Weiss, Mitch (Dutton, 2024)
"It's January 2, 1960: the day that Massachusetts Senator John F. Kennedy declared his candidacy; and with this opening scene, Chris Wallace offers readers a front-row seat to history. From the challenge of primary battles in a nation that had never elected a Catholic president, to the intense machinations of the national conventions--where JFK chose Lyndon B. Johnson as his running mate over the impassioned objections of his brother Bobby--this is a nonfiction political thriller filled with intrigue, cinematic action, and fresh reporting. Like with many popular histories, readers will be familiar with the story, but few will know the behind-the-scenes details, told here with gripping effect."--